Effect of the different sr dopant contents on NiO ceramic - N. N. M. Salim; J. J. Mohamed; Z.A. Ahmad (2015)
Sr - doped NiO ceramic was studied. The effect of composition variation of Ni(1-x)SrxO where x = 0, 0.01, 0.02, 0.03, 0.05 and 0.10 mole % was prepared by using solid state method. The calcination temperature used at 950 °C for 4 hours and the sintering temperature used at 1200 °C for 3 hours. The results depict the microstructures increase in grains size (0.43 - 3.30 μm) by increase of Sr dopant contents. The density and porosity testing support the result of microstructures analysis. The larger grains size led to increase in density and lower in porosity. The dielectric properties is observed in a wide frequency range of (1 - 1 000 MHz). The increase of dielectric constant is associated with the decrease of dielectric loss. The optimum composition was obtained for the x = 0.03 mole % sample with highest dielectric constant (3.24 x 103) and lowest dielectric loss (1.42) at 1 MHz.